Biological diversity conservation laws in South East Asia and Singapore: a regional approach in pursuit of the United Nations' Sustainable Development Goals?. (September 2016) - Ong, Burton; Lin-Heng, Lye; Chun, Dr Joseph
Abstract : Biodiversity and wildlife protection laws are integral to the pursuit of sustainable development, which the member states of the Association of South East Asian Nations (ASEAN) have had on their regional co-operation agenda for decades. This article provides an overview of the key legal and policy developments in ASEAN on this front, examining the central role of the 'soft law' approaches embraced by member states towards protecting and managing their mega-diverse genetic resources. The developments will be analysed through the lenses of the international law agreements which all ASEAN member states are party to: the Convention on Biological Diversity (CBD) and the Convention on International Trade in Endangered Species (CITES). While it may be sensible to adopt an integrated region-wide approach towards tackling the illicit activities (poaching, smuggling, biopiracy, etc) which threaten the region's biodiversity, the political landscape of ASEAN makes it unlikely for such a supra-national legal framework to emerge anytime soon. Harmonizing the national laws of the ASEAN member states will also be a challenge because of the vast differences between their respective socio-economic circumstances. To illustrate how the domestic concerns and priorities of each ASEAN member state shape the contours of their respective CBD- and CITES-implementing legislation, this article analyses the biodiversity and wildlife protection laws of Singapore – an extreme example within the ASEAN region because it is a land-scarce, densely populated, highly urbanized and economically advanced island state, quite unlike its enormous, populous and resource-rich neighbours. Despite Singapore's unique circumstances, the analysis reveals that there are elements of its legal and policy framework that are potentially transplantable to other legal systems within the region, though this will necessitate a more comprehensive comparative analysis of the relevant laws of the other ASEAN member states, which is beyond the scope of this article.